Rhodiola rosea L. Improves Learning and Memory Function: Preclinical Evidence and Possible Mechanisms - Ma, Gou-ping; Zheng, Qun; Xu, Meng-bei; Zhou, Xiao-li; Lu, Lin; Li, Zuo-xiao; Zheng, Guo-Qing (Frontiers in Pharmacology, 2018)
Rhodiola rosea L. (R. rosea L.) is widely used to stimulate the nervous system, extenuate anxiety, enhance work performance, relieve fatigue, and prevent high altitude sickness. Previous studies reported that R. rosea L. improves learning and memory function in animal models. Here, we conducted a systematic review and meta-analysis for preclinical studies to assess the current evidence for R. rosea L. effect on learning and memory function. Ultimately, 36 studies involving 836 animals were identified by searching 6 databases from inception to May 2018. The primary outcome measures included the escape latency in Morris water maze (MWM) test on behalf of learning ability, the frequency and the length of time spent on the target quadrant in MWM test representing memory function, and the number of errors in step down test, dark avoidance test and Y maze test on behalf of memory function. The secondary outcome measures were mechanisms of R. rosea L. for learning and/or memory function. Compared with control, the pooled results of 28 studies showed significant effects of R. rosea L. for reducing the escape latency (P<0.05); 23 studies for increasing the frequency and the length of time spent on the target quadrant (P<0.05); and 6 studies for decreasing the number of errors (P<0.01). The possible mechanisms of R. rosea L. are largely through antioxidant, cholinergic regulation, anti-apoptosis activities, anti-inflammatory, improving coronary blood flow and cerebral metabolism. In conclusion, the findings suggested that R. rosea L. can improve learning and memory function.